2016
DOI: 10.1074/jbc.m116.752121
|View full text |Cite
|
Sign up to set email alerts
|

IQGAP1 Interaction with RHO Family Proteins Revisited

Abstract: IQ motif-containing GTPase activating protein 1 (IQGAP1) plays a central role in the physical assembly of relevant signaling networks that are responsible for various cellular processes, including cell adhesion, polarity, and transmigration. The RHO family proteins CDC42 and RAC1 have been shown to mainly interact with the GAP-related domain (GRD) of IQGAP1. However, the role of its RASGAP C-terminal (RGCT) and C-terminal domains in the interactions with RHO proteins has remained obscure. Here, we demonstrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 77 publications
0
15
0
Order By: Relevance
“…Binding of Rac1/CDC42 to IQGAP1 is regulated by phosphorylation of IQGAP1 at two sites (Ser-1441 and -1443) ( 25 , 26 , 41 ). Detailed kinetic analysis showed that phosphorylation at Ser-1443 led to a decrease in the affinity of human IQGAP1 for Rac1 and CDC42 ( 27 ). To test whether LGR5 regulates IQGAP1–Rac1 interaction through modulation of IQGAP1 phosphorylation, we probed the level of phospho-IQGAP1 with an anti-phosphoserine antibody (no antibody specifically against Ser-1441 or Ser-1443 of IQGAP1 is available ( 42 )).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Binding of Rac1/CDC42 to IQGAP1 is regulated by phosphorylation of IQGAP1 at two sites (Ser-1441 and -1443) ( 25 , 26 , 41 ). Detailed kinetic analysis showed that phosphorylation at Ser-1443 led to a decrease in the affinity of human IQGAP1 for Rac1 and CDC42 ( 27 ). To test whether LGR5 regulates IQGAP1–Rac1 interaction through modulation of IQGAP1 phosphorylation, we probed the level of phospho-IQGAP1 with an anti-phosphoserine antibody (no antibody specifically against Ser-1441 or Ser-1443 of IQGAP1 is available ( 42 )).…”
Section: Resultsmentioning
confidence: 99%
“…Initially, we found that overexpression of LGR5 consistently led to increased binding of Rac1 and actin to IQGAP1 in co-IP analysis. Because it was reported that binding of Rac1/CDC42 to IQGAP1 is inhibited by phosphorylation at Ser-1441/1443 of IQGAP1 ( 26 , 27 , 41 ), we asked whether LGR5 modulates phosphorylation of IQGAP1 at these sites to regulate IQGAP1–Rac1 interaction. Indeed, LGR5 overexpression and KD of LGR5 led to a significant decrease and increase in Ser-1441/1443 phosphorylation, respectively, and LGR5 had no effect on PMA-induced phosphorylation of IQGAP1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports point to interaction between Rho family small GTPases with IQGAP1 C-terminal domains which could regulate Rho kinase-myosin II dependent retraction. Rho inhibitors disrupt the WRAMP complex in human melanoma cells [ 17 ] and IQGAP1 is known to interact with RhoA [ 43 , 44 ]. While promoting activity of RhoA, IQGAP1 may also decrease activity of Rac1 [ 45 ] in the cell tail during melanoma migration, which may require interactions with C-terminal domains of IQGAP1.…”
Section: Discussionmentioning
confidence: 99%
“…As an example, IQGAP proteins have been described as a scaffolding platform that assemble small GTPases, GEFs, and effectors. This association is a multi-step process that involves a high affinity binding of IQGAP1 to the switch regions of the small G-protein (a GTP-dependent event), and low affinity binding to an adjacent region (16). The described direct association of IQGAP1 with the Rac-GEF Tiam1 and Rac1 exemplifies the relevance of multiprotein complexes in Rac1 activation (17).…”
Section: Regulation Of Rac Activity: Nucleotide Binding Post-translamentioning
confidence: 99%